Operculectomy in The Pre-eruption Mandibular Third Molar is it Necessary?: A Case Report - Chaerita Maulani; Herwanda Dwi (YARSI Dental Scientific Meeting - e Journal, 2025)
Introduction: Pericoronitis is an inflammation of the soft tissue surrounding the crown of an impacted or partially erupted tooth, most commonly involving the mandibular third molar. This condition is caused by the accumulation of plaque and food debris beneath the operculum, which triggers bacterial infection. The management of pericoronitis can be performed either conservatively or definitively, one of which is operculectomy. Operculectomy is a minor surgical procedure to remove part of the operculum or tissue flap over an erupting tooth, especially the third molar. Operculectomy is indicated on third molars that are fully erupted, have an opposing tooth, are positioned vertically, have sufficient space for eruption, are intended as abutments for fixed prostheses, or when the patient refuses extraction. Contraindications include third molars that are not fully erupted, horizontally positioned, or lack an opposing tooth. Case Report: A 24-year-old female patient presented with a complaint of the lower right third molar being partially has operculum, causing pain during mastication. Intraoral examination showed missing teeth in two teeth, caries in six teeth, gangrene radix in tooth 36, and pre-eruption of tooth 48. The patient had no history of systemic disease. Discussion: The patient was diagnosed with pericoronitis in the operculum region of tooth 48. Clinical findings included hyperemia, swelling, bleeding, and food impaction. An operculectomy was performed after initial therapy. Follow-up evaluation showed significant improvement within two weeks post-treatment without scar formation. Conclusion: Operculectomy is an effective treatment option for managing pericoronitis of the mandibular third molar, with a good prognosis when accompanied by optimal oral hygiene maintenance.